Towards sustainability of EA practices: A systematic review - Hussein, Surya Sumarni; Ismail, Zuraini; Mat Taib, Mohamad Zainuddi (2016)
Enterprise Architecture (EA) has been identified as one of the prime initiative to drive the establishment of connected government towards world class public service delivery.However, building upon several public sector agencies that had implemented these initiatives, it was reported as unfavourable in sustaining EA practices.This study aims to i. review and identify related issues ii. Identify factors that influence sustainability of EA practices also iii. Identify elements of EA governance.Through the systematic literature review (SLR) five related issues were discerned, four key factors were established in sustaining EA practices while five elements of EA governance emerged in the construction of EA governance framework.